(untitled) (2014)
Pyrogallol[4]arenes are macrocycles with high potential as building blocks for nanocapsules. We theoretically studied the dimeric precursors of 2,8,14,20-tetramethylpyrogallol[4]arene and 2,8,10,14-tetraphenylpyrogallol[4]arene to understand the dynamics of assembly of these compounds, and calculated the potential energy curves along the torsion angle of the (R-pyrogallol)CH–(R-pyrogallol) dimeric bond at the B3LYP/6-311G(d,p) level of theory. We found that the energy barriers for free rotation around the selected bond are 0.00133 Hartrees for the alkyl-substituted dimer and 0.77879 Hartrees for the aryl-substituted dimer. These values imply that the free rotation around the selected bond exists for the first dimer but not for the second one. Because the orientation of the substituent and the pyrogallol ring around this bond are likely to determine the geometry of the final structure, we propose that the alkyl-substituted compound will most likely adopt a crown-shaped geometry whereas the aryl-substituted compound will adopt a chair-shaped geometry. These predictions concur with experimental evidence, which shows that the geometry of pyrogallol[4]arenes depends on the substituents attached to them.